Teacher's Efforts in Strengthening Religious Character in the Time of the COVID-19 Pandemic in Grade 1 Elementary School Students: Upaya Guru dalam Penguatan Karakter Religius di Masa Pandemi COVID-19 pada Siswa SD Kelas 1 - Ummah, Putri Rochmatul; Supriyadi, Supriyadi (Universitas Muhammadiyah Sidoarjo, 2022)
Education is a process of forming individuals who are not only cognitively, scientifically and philosophically intelligent but also able to develop their social and spiritual attitudes. The phenomenon that occurs is that the whole world is being hit by the COVID-19 outbreak, this causes students to study at home. The teacher does not use the pandemic as an excuse that hinders the process of strengthening the religious character of students. The purpose of this study is to describe how the teacher's efforts in strengthening religious character during the COVID-19 pandemic in grade 1 students of SD Muhammadiyah 1 Krembung. This research approach is descriptive qualitative with phenomenological research type. The results of this study indicate that the teacher's efforts in strengthening the religious character of grade 1 students during the pandemic are carried out through 2 stages: 1) The planning stage includes integrating religious characters in the lesson plans, compiling indicators of religious character; 2) The implementation phase includes habituation of school culture such as praying before and after starting learning, praying dhuha at home, memorizing short letters, reading daily prayers, and helping parents at home.